2013
DOI: 10.1038/onc.2013.520
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell origin of myelodysplastic syndromes

Abstract: Myelodysplastic syndromes (MDS) are common hematologic disorders that are characterized by decreased blood counts due to ineffective hematopoiesis. MDS is considered a 'preleukemic' disorder linked to a significantly elevated risk of developing an overt acute leukemia. Cytopenias can be observed in all three myeloid lineages suggesting the involvement of multipotent, immature hematopoietic cells in the pathophysiology of this disease. Recent studies using murine models of MDS as well as primary patient-derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 129 publications
2
45
0
1
Order By: Relevance
“…Leukemia-initiating stem cells including preleukemic stem cells have been shown to persist even during morphologic remissions after these treatments and have to be targeted for future curative approaches. 1,2,8,9,20,41 It has been shown that leukemia-initiating cells can reside in different phenotypic stem and progenitor compartments at relatively low frequencies and are associated with transcription factor alterations that result in pathogenic transcriptional changes. [2][3][4][5][6][7][11][12][13]32,[42][43][44] Thus, to uncover newer stem cell-directed targets, we conducted a transcriptomic analysis on rigorously defined stem and progenitor populations in AML and MDS in comparison with their respective healthy counterparts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leukemia-initiating stem cells including preleukemic stem cells have been shown to persist even during morphologic remissions after these treatments and have to be targeted for future curative approaches. 1,2,8,9,20,41 It has been shown that leukemia-initiating cells can reside in different phenotypic stem and progenitor compartments at relatively low frequencies and are associated with transcription factor alterations that result in pathogenic transcriptional changes. [2][3][4][5][6][7][11][12][13]32,[42][43][44] Thus, to uncover newer stem cell-directed targets, we conducted a transcriptomic analysis on rigorously defined stem and progenitor populations in AML and MDS in comparison with their respective healthy counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Despite the use of poly-chemotherapy and the development of newer agents, clinical outcome remains poor. The disease course is frequently characterized by relapse or failure to achieve durable remission, indicating that current treatment regimens do not target the cancer-initiating cells.…”
Section: Introductionmentioning
confidence: 99%
“…Myelodysplastic syndromes (MDS) are clonal disorders that arise from genetic and/or epigenetics damage in hematopoietic stem cells [1]. MDS are clinically heterogeneous characterized by varying degrees of cytopenias and a high risk of progression to acute myeloid leukemia (AML) [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…4 In parallel, involvement of a multipotent CD34 1 /CD38 2 HPC has also been demonstrated in other myeloproliferative neoplasms (MPNs), myelodysplastic syndromes (MDSs), [17][18][19] and acute myeloid leukemia. 20,21 Moreover, the AHNMD cells from SM-AHNMD patients often carry the KIT D816V mutation, [22][23][24] supporting a common clonal origin for both disease components in an HPC with multilineage potential.…”
Section: Introductionmentioning
confidence: 99%